Intraoral Lymphomatoid Papulosis Type D Showing Scarce/Absent CD30 Expression in A Pediatric Patient: Case Report and Literature Review - Palaçon, Mariana Paravani [UNESP]; Marques, Marcelo Borges [UNESP]; Silveira, Débora Fernandes Mendes [UNESP]; Martins, Karina Helen; Silveira, Heitor Albergoni; Pereira-Filho, Valfrido Antonio [UNESP]; Bufalino, Andreia [UNESP]; Chahud, Fernando; León, Jorge Esquiche (Springer Nature, 2025)
Purpose: Approximately 10% of all lymphomatoid papulosis (LyP) cases affect pediatric patients. Pediatric LyP is clinically similar to adult LyP, frequently with cutaneous involvement, whereas the affectation of mucosal surface is rare. The LyP clinicopathological spectrum includes type A, B, C, D, E, and LyP with DUSP22/IRF4 rearrangement, with LyP type D representing < 5% of all LyP cases. Methods: We have previously reported 2 cases of exclusively intraoral LyP type C and E. To date, about 50 cases of LyP type D have been reported; of them, 8 cases, all but one with exclusive skin involvement, corresponded to pediatric patients. Rare LyP type C cases can lack CD30 expression, creating diagnostic difficulties with lymphoma. Results: Here, we report an extremely rare case of intraoral LyP type D with scarce/absent CD30 expression affecting a 12-year-old white Brazilian boy. Conclusions: To our best knowledge, this is the first pediatric case of LyP type D with exclusive intraoral involvement.
Keywords: CD30; Differential diagnosis; Lymphomatoid papulosis type D; Oral cavity; Pediatric patients